2019
DOI: 10.1186/s12884-019-2528-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sanitation practices on adverse pregnancy outcomes in India: a conducive finding from recent Indian demographic health survey

Abstract: BackgroundSeveral risk factors predisposing women and their live-borns to adverse outcomes during pregnancy have been documented. Little is known about sanitation being a factor contributing to adverse pregnancy outcomes in India. The role of sanitation in adverse pregnancy outcomes remains largely unexplored in the Indian context. This study is an attempt to bring the focus on sanitation as a factor in adverse pregnancy outcome. Along with the sanitation factors, few confounder variables have also been studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…In our study, lack of latrine utilization was also a statistically significant factor for low birth weight in which pregnant women who utilized latrine were 53% less likely to have low birth weighted newborns compared to their counterparts. Similar findings were reported from other studies conducted in Southwest Ethiopia [ 36 ], India [ 38 ]. Poor or no utilization of latrine could reflect fecal contamination of the local environment which in turn could result in a high incidence of infectious disease and intestinal parasites, thus high levels of nutrient mal-absorption in pregnant women and the possibility to have low birth weight newborns.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, lack of latrine utilization was also a statistically significant factor for low birth weight in which pregnant women who utilized latrine were 53% less likely to have low birth weighted newborns compared to their counterparts. Similar findings were reported from other studies conducted in Southwest Ethiopia [ 36 ], India [ 38 ]. Poor or no utilization of latrine could reflect fecal contamination of the local environment which in turn could result in a high incidence of infectious disease and intestinal parasites, thus high levels of nutrient mal-absorption in pregnant women and the possibility to have low birth weight newborns.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, in 2014, only 52% of deliveries were attended by a skilled health professional [ 10 ]. While research has demonstrated the importance of water, sanitation, and hygiene (WASH) for maternal and child health (MCH) [ 11 , 12 ], access to improved water and sanitation facilities and use of basic MCH health services have rarely been considered together. Recently, a handful of programs that aimed to increase women’s use of antenatal care services also included water treatment [ 13 ] and hygiene education [ 14 , 15 ], pointing towards potential opportunities for MCH and WASH integrated intervention strategies in resource constraint setting.…”
Section: Introductionmentioning
confidence: 99%
“…This range went from 14.0 kg (underweight women) to less than 6.0 kg for obesity grade 3 (BMI ≥ 40 kg/m 2 ) 29 . Gestational weight gained outside this range was associated with low and moderate adverse outcomes 30 . A population‐based study in the United States of pregnant women with singleton hospital births between 2004 and 2013 found that both low and excess weight gain were associated with severe adverse birth outcomes 31 .…”
Section: Discussionmentioning
confidence: 99%